Palmar and plantar fibromatosis: a review - Brian D. Stewart; Alessandra F. Nascimento (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Palmar fibromatosis (Dupuytren disease/contracture) is the most common type of fibromatosis, defined as a benign proliferation of fibroblasts and myofibroblasts. The disease process is most common in white, middle-aged and older men occurring at the distal palmar crease leading to nodules and contracture, which in many cases recur after surgical treatment. In a similar process, plantar fibromatosis (Ledderhose disease) is a proliferation of fibroblasts and myofibroblasts on the plantar aponeurosis of mostly middle-aged patients that may lead to painful nodules but usually does not lead to contracture. Both processes are histologically similar, composed of a bland cellular proliferation of spindle cells with a bluish appearance and with a variable amount of background collagen, depending on the age of the lesion. The etiology of both lesions is still uncertain, while treatment ranges from observation to surgery, with some pharmacologic agents being investigated with mixed success. In this paper we provide an overview of both processes with regards to clinical and radiologic findings, pathophysiology, diagnosis, treatment, and prognosis.